Mechanical properties and crystallinity of linear low density polyethylene based biocomposite film - Dodi Irwanto; Bidhari Pidhatika; Dwi Wahini Nurhajati; Syaiful Harjanto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2019)
Cassava starch filled linear low-density polyethylene (LLDPE) films are made in order to make plastics which environmentally friendly. The use of compatibilizer ethylene - acrylic ester - maleic anhydride polymerized is needed to obtain a compatible mixture of starch which is hydrophilic and LLDPE which is hydrophobic. In this study LLDPE films obtained were tested for tensile strength and elongation before and after accelerated aging and density. Melt flow index (MFI) of the film was also measured to determine the rheological properties. Crystallinity has been done by an X-Ray diffraction. The results showed that the addition of thermoplastic starch tended to reduce the tensile strength, elongation, and MFI values but increase the density of LLDPE films. The aging process at a temperature of 70°C ± 2°C for 168 hours ± 2 hours tends to increase the tensile strength but decrease the extension of the break.